A governanca no arranjo produtivo local metal-mecânico automotivo da serra gaúcha - Patias, Tiago Zardin (My University, 2014)
This work analyses the governance of the local productive arrangement (APL) named Metalmecânico Automotivo da Serra Gaúcha (APLMMA), which includes more than 2,700 firms, most of them small and micro enterprises, comprising the second largest metal-mechanic conglomeration in Brazil. The main purpose of the research is to study the type of governance of the APLMMA. The specific goals are: a) to recover the history of the APLMMA; b) to establish a relationship between existing theories about governance and what is practiced inside the APLMMA; c) to identify and analyze a governance model that can fit other APL's. The governance of the APLMMA is carry out by epresentatives of six local and regional entities, which plan and implement useful activities for the APL. The exploratory research was carried out thru a single case study, by using semi-structured interviews applied to six representatives, as well as other sources of information such as APLMMA documents research, literature, and simple observation. Content analysis was done on the collected data, resulting on a categorization of elements followed by a comparison with the review of literature. The main results show that despite the fact that the APLMMA is considered a national prime example, it cannot be considered a full-grown APL. It can rather be labeled an APL under construction. The results also indicate that the term governance may not be the most adequate sentence to be used for a research on APL's, once most of the researchers do not use this term and most of the literature publication is related to productive chain itself. It is apparent that the APLMMA could benefit from past experiences with regional development agencies in Italy and in the state of Santa Catarina (Brazil), in order to improve its own management system as well as to promote regional development. Finally, limitations of the study and suggestions for future research are addressed.
Este trabalho analisa a governança do Arranjo Produtivo Local Metalmecânico Automotivo da Serra Gaúcha (APLMMA), arranjo este composto por mais de 2.700 empresas, a maioria micro e pequenas, inseridas no segundo maior pólo metalmecânico do Brasil. O objetivo principal da pesquisa é compreender a forma de governança do APLMMA. Os objetivos específicos são: a) resgatar a história do APL; b) relacionar a teoria existente sobre governança com a prática do APL; e c) identificar e analisar um possível modelo de governança que seja adequado a outros APL's. A governança no APLMMA é exercida por representantes de seis entidades locais e regionais, que procuram planejar ações conjuntas em prol do APL. A pesquisa exploratória é sobre um estudo de caso único, com a realização de entrevistas parcialmente estruturadas com os representantes das entidades que formam a governança do APL, bem como com outras fontes de coleta de evidências, como pesquisa documental, bibliográfica e observação simples. Com as informações coletadas foi realizada uma análise de conteúdo, com a conseqüente categorização e posterior comparação com a revisão teórica realizada. Os principais resultados obtidos mostram que apesar do APLMMA ser considerado referência nacional, ainda não pode ser considerado um arranjo produtivo completo, mas sim um arranjo em formação; que o termo governança pode não ser o mais adequado para pesquisas em APL's, tendo em vista que a maioria destas não utiliza esta nomenclatura e as referências teóricas são relacionadas com as cadeias produtivas, o que não é bem o caso de um APL; que há a necessidade de se utilizar as experiências italianas e catarinenses sobre agências de desenvolvimento regional, para aprimorar a gestão do APLMMA bem como promover um maior desenvolvimento regional. Por fim, apontam-se algumas limitações da investigação bem como possibilidades de pesquisas futuras.
Keywords: Administração de empresas; Governança; Arranjos Produtivos Locais (APLs); Setor metal-mecânico; Aglomerados industriais; Serra gaúcha; Governance; Local Productive Arrangements; Metal-mechanic